Composition and screening of antifungal activity against Cladosporium sphaerospermum and Cladosporium cladosporioides of essential oils of leaves and fruits of Piper species - Morandim, Andreia de A. [UNESP]; Pin, Aline R.; Pietro, Natalia A. S.; Alecio, Alberto C. [UNESP]; Kato, Massuo J.; Young, Claudia M.; de Oliveira, José E. [UNESP]; Furlan, Maysa [UNESP] (My University, 2010)
This study investigated the composition and antifungal activity against Cladosporium sphaerospermum and Cladosporium cladosporioides of essential oils of leaves of Piper cernuum, Piper diospyrifolium, Piper crassinervium, Piper solmsianum and Piper umbelata and fruits of P. cernuum and P. diospyrifolium. The essentials oils were analyzed by GC-MS and submitted of the antifungal activity tests. The essential oils of fruits from P. cernuum and leaves of P. crassinervium and P. solmsianum showed potential antifungal activity against C. sphaerospermum and C. cladosporioides. In addition, this is the first report of the composition of essential oils of fruits of P. cernuum and P. diospyrifolium. © 2010 Academic Journals.
Keywords: Antifungal activity; Essential oil composition; GC-MS; Piper; Piperaceae